Reproducible research - Magle, C. Tobin, speaker (Colorado State University. Libraries, 2017)
What is reproducible research? Why should you adopt it? How to use R, git and markdown to make your analysis more efficient and reproducible.
Data and donuts
ZIP file contains: instructional materials.
Accessibility features: Transcript.
Keywords: data management; data storage; data education; Data editing; Data curation; Programming languages (Electronic computers)